"The Rise of the Phoenix": Empowering Learners to Create Their Own Learning Cultures and Transform Their School. Issue 4 (October 2021) - McCallister, Cynthia
An account of a persistently failing New York City high school's rapid transformation. Urban Assembly School for Green Careers had a 39% graduation rate in 2013 and ranked in the bottom 1% of high schools citywide. As a transformation strategy, the school employed an innovative educational design known as Learning Cultures, which distributes responsibility for learning to learners. After the first year of implementation the graduation rate rose by 11%. After two years of implementation the school received a "well developed" rating on its external quality review. After 4 years the graduation rate doubled. This report describes the school design and provides an account of educational outcomes.